PENGETAHUAN IBU MENGENAI APLIKASI KESEHATAN ANAK SEBUAH STUDI DESKRIPTIF - Astri Indika Husna (Indonesian Journal of Health Development, 2021)
Background: Children's Health Applications is one of the internet-based technology media that parents can use to monitor children's growth and development at home. DKI Jakarta and Java are the highest cases of growth and health problems in children under five, with 143.26 million people out of 262 million. Objective: this study aims to measure maternal knowledge regarding child health applications. Method: This type of research uses descriptive research, with research population of mothers who live in the Posyandu Region of Segarajaya Village, Bekasi Regency. The sampling used is the Non-Probability method with the Purposive Sampling technique. Results: Obtained analysis results from a sample of 124 respondents, found the age of mothers under five with an average age of 30.65 years, secondary education level of 72 respondents (58.1%), not working as many as 101 respondents (81.5% ), and have very good knowledge about child health applications as many as 92 respondents (74.2%). Conclusion: The level of knowledge about Child Health Applications in the most research respondents falls into the excellent category. Recommendation: Suggest further research to plan the implementation of counseling on Child Health Applications because there are still toddlers who still have less knowledge of health technology media, as well as increase the knowledge of toddler mothers by updating information related to Child Health Applications.